Trade with China, inequality and policy responses - Wolfgang Lechthaler; Mariya Mileva (Intereconomics, 2015)
The integration of China's huge workforce into the global trading system has had profound effects on economies worldwide. Trade with China has been shown to lead to wage losses and declining employment in developed countries. The integration of the Chinese economy into the world trade is also frequently blamed for rising inequality. This article analyses policy instruments that can remedy the rising levels of income inequality in industrialised countries, differentiating between the short-term causes, e.g. the slow reallocation of workers across sectors, and the long-term ones, e.g. the increased demand for skilled workers. Instruments considered include a general wage tax, sector-specific taxes on consumption and profit, tailored subsidies for firms, and training subsidies.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Handelsliberalisierung; Internationale Handelspolitik; Einkommensverteilung; Verteilungspolitik; Industrieländer; China